NON-FINANCIAL (SOCIAL) REPORTING OF ENTERPRISES - Kaminska, I. B. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The activation of the processes of implementing the concept of corporate social responsibility of business in Ukraine has predetermined the need to study foreign experience in reporting of such implementation results. Confirmation of the implementation of the principles and provisions of corporate social responsibility concept as a full-fledged business development strategy predetermines reporting to relevant stakeholders about relevant developments or, conversely, non-compliance with the requirements of this strategy. Reporting forms, reporting principles, and dissemination of reporting data are the main issues that were arised at the stage of the final dialogue with stakeholders.The article defines the economic essence of the concept of "non-financial (social) reporting" as a documented set of a commercial organization data that reflects the company's environment, principles and methods of cooperation with groups of influence, results of the company's activities in the economic, social and environmental spheres of society's life. The theoretical aspects of forms and types of non-financial (social) reporting, approaches to its compilation are also considered. Problems of adaptation of foreign practice of business activity on the basis of corporate social responsibility and preparation of non-financial reporting to the national accounting and business practices are defined. The study found that 83 % of Ukrainian companies implement the concept of corporate social responsibility in their activities. However, the declarativeness and low level of domestic social reports verification indicate lack of a good understanding by the management link that non-financial reporting is not a promotional document , but a demonstrating tool of corporate maturity in matters of responsibility for taken business decisions. In Ukraine, the preparation of non-financial reports is still the prerogative of large national companies and representations of international corporations. However, an increase in the number of non-financial reports compiled according to the GRI standard has observed recently in Ukraine. Further scientific researches should address to the need of social accounting maintaining in the enterprise as the basis for drawing up non-financial reporting.